Familial Mediterranean fever without cardinal symptoms and role of genetic screening - I. Hacıbekiroglu; M.S. Dal; C. Bes; H. Buyukhatipoglu; T. Ulas; H.G. Apucu; F. Borlu (PAGEPress Publications, 2012)
Familial mediterranean fever is an autosomal recessive disorder characterized by paroxysmal episodes of fever and serosal inflammation. The classical presentation is fever and severe recurrent abdominal pain due to serositis that lasts for one to three days and the resolves spontaneously. Between the episodes patients are asymptomatic. Ninety-five percent of patients with familial mediterranean fever have painful episodes localized to the abdomen, which is usually the dominant manifestation of the disease. Herein, we present a case of 34-year-old man with incomplete abdominal pain episode of familial mediterranean fever limited to the epigastrum and had no cardinals symptoms of this disease. The diagnosis was made by genetic screening. Succesful treatment response was achieved by colchicine.